A novel approach to systematically implement the universal definition of myocardial infarction: insights from the CHAMPION PLATFORM trial. Issue 17 (23rd February 2013) - Leonardi, Sergio; Truffa, Adriano A M; Neely, Megan L; Tricoci, Pierluigi; White, Harvey D; Gibson, C Michael; Wilson, Matthew; Stone, Gregg W; Harrington, Robert A; Bhatt, Deepak L; Mahaffey, Kenneth W
Abstract : Objective: To reassess the efficacy of cangrelor efficacy using the universal definition of myocardial infarction (MI). Design: We adopted a novel approach to systematically implement the universal definition of MI. Two physicians blinded to treatment allocation reviewed plots of CK-MB and troponin values in relation to time of randomisation and percutaneous coronary intervention (PCI) to identify patients with stable or falling biomarkers pre-PCI (ie, primary cohort), and those with post-PCI CK-MB elevations. Setting: The CHAMPION PLATFORM trial. Patients: Non-ST-elevation acute coronary syndromes (95%) and stable angina patients (5%). Interventions: Cangrelor versus placebo. Main outcome measures: The efficacy of cangrelor compared with placebo using the reclassified events (type 4a MI) and the original clinical events committee-adjudicated (CEC PCI-MI) results was investigated. Results: Of 5295 patients, 3406 (64.4%) were in the primary cohort. Type 4a MI occurred in 4.3% (226 events/5295 patients) while original CEC PCI-MI occurred in 6.5% (344 events/5295 patients), a significant difference (p<0.0001). Using the reclassified MI events, the primary composite endpoint of death, MI, or ischaemia-driven revascularisation through 48 h occurred in 5.4% of patients (4.9% cangrelor, 6.0% placebo; OR 0.80; 95% CI 0.63 to 1.02) as opposed to 7.5% of the primary analyses (7.0% cangrelor, 8.0% placebo; OR 0.87; 95% CI 0.71 to 1.07). Conclusions: Systematic, strict implementation of the universal MI definition with emphasis on baseline assessment may enhance discrimination in detecting PCI-MI and may allow for more rigorous assessment of interventions in patients undergoing early PCI.